Anxiety and depression and health-related quality of life among adults with migraine: a National Population-Based Study - Monira Alwhaibi; Monira Alwhaibi; Bander Balkhi; Bander Balkhi; Yazed AlRuthia; Yazed AlRuthia (Frontiers Media S.A., 2023)
BackgroundAdults who suffer from migraines are highly susceptible to mental illnesses that may have significant association with their HRQoL. Therefore, this study aimed to investigate how anxiety and depression related to HRQoL in adults with Migraine.MethodsData from the Medical Expenditure Panel Survey for 2017 to 2020 were used to identify adult patients 18 years of age and older with a migraine diagnosis. The Physical and Mental Component Summary (PCS & MCS) scores from the SF-12 were used to calculate HRQoL. To adjust for a wide range of variables, multivariate linear regressions were used to evaluate the association between depression and anxiety and HRQoL among adults with migraine.ResultsAmong the 1,713 identified adults with migraines, 11.2% experienced depression, 14.6% experienced anxiety, and 13.7% had both conditions. Compared to migraineurs who had only migraine, adults with comorbid depression and anxiety had the lowest mean scores on the PCS and MCS. Additionally, migraineurs who had depression had significantly lower HRQoL MCS scores (depression: β = −7.552, p < 0.001), and those with anxiety had significantly lower HRQoL MCS scores (anxiety: β = −4.844, p < 0.001) compared to those without these comorbidities. Notably, individuals with migraines who exercise had higher scores on both PCS and MCS than those who did not exercise.ConclusionThis nationally representative sample provides insights into the associations between depression and anxiety with poor HRQoL among individuals with migraines. Additionally, it revealed the negative impact of concurrent chronic diseases, and poor socioeconomic status on HRQoL, while emphasizing the beneficial effects of regular exercise. This study highlights the clinical, policy, and public health implications for improving healthcare planning, resource allocation, and promoting lifestyle changes to reduce depression and anxiety in migraine sufferers.